O-06 Motor cortex excitability and conduction time of pyramidal tracts in preclinical SCA1 gene carriers. Issue 7 (July 2019) - Rakowicz, Maria; Rola, Rafal; Sobanska, Anna; Antczak, Jakub; Inglot, Ewa; Sulek, Anna
Abstract : Background: Spinocerebellar ataxia type 1 (SCA1) is a neurodegenerative, dominantly inherited disease caused by CAG repeat expansion. It manifests mainly as trunk and limbs ataxia, dysarthria, gaze palsy and peripheral neuropathy. We aimed to assess the functional alterations of corticospinal tracts in preclinical SCA1 gene carriers performed during 4-years follow-up. Methods: Transcranial magnetic stimulation (TMS) was carried out in 26 SCA1 gene carries with age at study entry 25.6 ± 4.7, CAG repeat number 49.5 ± 4.8 and 30 age- and gender-matched healthy controls (HC). Presence of ataxia was assessed by the Scale for Assessment and Rating of Ataxia (SARA). TMS was performed every ± 12 months to evaluate motor threshold (MT), silent period (SP) from hypothenar and extensor digitorum brevis muscles, central motor conduction time (CMCT) and motor evoked potentials amplitude (MEPs). Results: Baseline SARA score increased from 0.6 ± 0.7 to 4.9 ± 5.2 points across follow-up. In 43% SCA1 cases MT of lower limbs was elevated and MEPs were in 35% decreased. SP was longer (p < 0.01) in SCA1 cases than in HC and revealed prolongation in 86% of subjects from baseline to the last assessment. CMCT to the lumbar spinal cord segments was prolonged in 46% of cases at the first examination. At the last assessment it was significantly longer (p < 0.0001) to the cervical and lumbar segments. Conclusions: In the preclinical SCA1 gene carriers before the onset of overt clinical signs TMS revealed functional alterations of corticospinal pathways. TMS could serve as an objective measure of disease progression in SCA1 patients.